The Effect of Self-monitoring Therapy on Academic Achievement and Behavior among College Students - Mehdi Mehri Shahabadi; Megha Uplane; Vibhawari B. Nikam (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
in performance and maladaptive behaviours among college students, underscoring the need for effective psychological interventions. Objective: This study aims to examine the effect of self-monitoring therapy on improving academic achievement and behaviour among college students. Method: An experimental one-group pretest–posttest design was employed. The participants were 10 Department of Education and Extension students selected as research subjects. Data were collected using validated academic achievement and behaviour scales, along with structured treatment guidelines. The data were analysed using the nonparametric Wilcoxon Signed Rank Test to assess differences before and after the intervention. Result: The findings indicate a statistically significant improvement in both academic achievement and student behaviour following the implementation of self-monitoring therapy. These findings demonstrate that self-monitoring therapy is effective in enhancing college students’ academic performance and promoting positive behavioural changes. Conclusion: Self-monitoring therapy can be considered a practical intervention strategy in educational settings. Contribution: This study contributes to the development of educational and counseling psychology by providing empirical evidence on the effectiveness of intervention-based approaches to improving student outcomes.